Innovative gel method: Sustainable crack healing in ceramic powder geopolymer mortars via marine actinomycetes and bioactivated carriers - Koseoglu, Sumeyye; Kubat, Merve; Uysal, Mucteba; Aydogdu, Elif Ozlem Arslan; Aygun, Beyza Fahriye; Canpolat, Orhan (ELSEVIER, 2025)
This study addresses the urgent need for efficient self-healing methods in geopolymer mortars (GMs), which, with their favorable low-carbon character, are still vulnerable to microcracking and ongoing durability loss. GMs made of 50 % ceramic powder (CP) and 50% granulated blast furnace slag (GBFS), synthesized with sodium hydroxide (2-12 M) and sodium silicate (Na2SiO3/ NaOH = 1.0-2.0) at an initial sand-to-binder ratio of 2.5, were cured at temperatures of 40 degrees C to 100 degrees C. Artificial microcracks with diameters of 0.2 mm and 0.6 mm were created before applying liquid (+S) and gel-like (+J) formulations of S. pasteurii and marine actinomycetes isolated from Marmara Sea sediments for 90-day treatments. Compressive and flexural strength, water absorption, ultrasonic pulse velocity (UPV), and microstructural analyses via SEM/EDS, XRD, and FTIR were considered methods for assessing healing performance. The S1 +S group showed the best mechanical recovery, with compressive and flexural strengths of 42.92 MPa and 8.98 MPa, respectively, while S26 +S showed the best UPV value of 3245.44 m/s, attesting to effective internal consolidation. S13 +S showed the most balanced improvement in acetate-decomposing strains, with compressive strength of 37.20 MPa, flexural strength of 5.63 MPa, and minimized water absorption (7.44 %). Preservation of calcite precipitation and crystalline geopolymeric phases were confirmed via XRD. At the same time, increased carbonate and Si-O-Al bonding in FTIR indicated that the microbe-induced and inorganic polymerized structures occurred simultaneously. EDS also supported these findings, where increased Ca and C contents asserted localized CaCO3 accumulation and increased peaks for Si and Al confirmed the unstable geopolymerization. All these findings place marine actinomycetes-especially acetate-decomposing strains-at the forefront of prospects for self-sustaining crack healing and structural reinforcement in green GMs.
Keywords: Bio-activated geopolymer mortars; Waste ceramic powder; Microbial calcium carbonate precipitation; Marine actinomycete; BACTERIA; Construction & Building Technology; Engineering; Materials Science